ADVANCE CARE PLANNING AND THE LAW: UNINTENDED BARRIERS. Issue 2 (1st June 2013) - Cartwright, C; Brownie, S
Abstract : Background: Under the Australian Constitution, each state/territory of Australia has responsibility for developing its own health law. Over the last 25 years, Advance Care Planning legislation in Australia has developed at a different rate, and with different emphasis, in each state/territory, resulting in different legislation, documentation and terminology in each state/territory. While there is some support for more national consistency, it is important to understand the current legislative provisions and the often unintended barriers to some aspects of ACP created by the law in various jurisdictions. Aim: The aim of this project was to compare legislation across each state/territory, to support two national information seminar series across Australia in 2011 and 2012. Methods: ACP legislation was examined and compared for each state/territory. As part of the seminar series, stakeholders in each state/territory were asked to alert the presenter if their understanding of their legislation was different to what was presented. When this happened, the presenter subsequently clarified the issue. Results: Issues were identified in most states/territories that could be disincentives to effective ACP. Discussion: Problems identified included incorrect assumptions in NSW and Tasmania that Advance Directives were not legally binding; confusion in NSW about the authority of the Person Responsible to refuse life-sustaining treatment; and inherent problems in South Australia resulting from there being no order of authority for substitute decision-makers. Conclusion: Ensuring individual wishes/directions for future health care/medical treatment are respected requires that problems with state/territory legislation be addressed as a matter of urgency.